2019
DOI: 10.1111/tbed.13380
|View full text |Cite
|
Sign up to set email alerts
|

Novel H5N6 avian influenza virus reassortants with European H5N8 isolated in migratory birds, China

Abstract: Five novel H5N6 influenza viruses, including four highly pathogenic avian influenza viruses and one low pathogenic avian influenza virus, were isolated from migratory birds in Ningxia, China, in November 2017. To understand the genetic origination of the novel H5N6 virus, and the infectivity and pathogenicity of the four highly pathogenic avian influenza viruses in mammals, phylogeographic analyses and infection studies in mice were performed. The phylogenetic and phylogeographic analyses showed that the H5N6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…The long branch lengths for all segments of the East Asian lineage compared with those for strains from Europe suggested that the virus had been circulating undetected for the intervening period and seemed to have a common ancestor from older viruses during early 2020 or 2019 (Appendix Figure 4). A previous study of the origin of clade 2.3.4.4b HPAI H5N6 viruses isolated in wild ducks in Ningxia in 2017 indicated a similar transmission pattern (15). In addition, isolate NX-105 showed an extremely close phylogenetic relationship with the 2020 isolates from Russia (Appendix Figure 4), which also seemed to be transmitted to China by migratory wild ducks.…”
Section: Discussionmentioning
confidence: 58%
“…The long branch lengths for all segments of the East Asian lineage compared with those for strains from Europe suggested that the virus had been circulating undetected for the intervening period and seemed to have a common ancestor from older viruses during early 2020 or 2019 (Appendix Figure 4). A previous study of the origin of clade 2.3.4.4b HPAI H5N6 viruses isolated in wild ducks in Ningxia in 2017 indicated a similar transmission pattern (15). In addition, isolate NX-105 showed an extremely close phylogenetic relationship with the 2020 isolates from Russia (Appendix Figure 4), which also seemed to be transmitted to China by migratory wild ducks.…”
Section: Discussionmentioning
confidence: 58%
“…The avian influenza virus will be spread by wild birds that are bringing it to the nations along the migration flyways. Domestic poultry and wild birds may reassort and exchange genes, creating new reassortant strains or adaptive mutations [ 61 , 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Yellow River Delta Nature Reserve is located on the East Asian‐Australasian flyway and is famous for an overwintering and stopover habitat for migratory wild birds (Han et al., 2019). Wild birds are generally considered as the natural reservoirs of avian influenza viruses, especially those live‐in wetlands and aquatic environments (Kalonda et al., 2020; Sun et al., 2020). Migratory wild birds that carry AIVs might spread the virus into the stopover habitats via their migratory flyways and might contribute to the global spread of the H5N8 virus (Global Consortium for H5N8 & Related Influenza Viruses, 2016 ; Rohaim et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Available evidence strongly indicates that the highly pathogenic avian influenza (HPAI) H5N8 viruses were introduced and spread across the globe via migratory wild birds (Verhagen et al., 2015). Migratory wild birds have been widely demonstrated that they lead to long‐distance transmission and reassortment of HPAI through their migration flyways while they migrated between wintering and breeding spots seasonally (Global Consortium for H5N8 & Related Influenza Viruses, 2016 ; Sun et al., 2020). The geographical location of Shandong makes it a crucial migration habitat for migratory birds to take a rest when crossing East Asia and Australia (Olsen et al., 2006).…”
Section: Introductionmentioning
confidence: 99%